Pelatihan Ekoliterasi dalam Pembelajaran Bahasa Indonesia dan PPKn Bagi Guru Bidang Studi dan Siswa-Siswa dengan Menggunakan Metode SQ3R Di SMP Negeri 1 Kefamenanu - Nahak, Maria Magdalena Namok; Feka, Yanuarius Sani; Keraf, Fransiskus Markus Pereto (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
Community service activities are activities that include literacy movement efforts in supporting environmental conservation programs that become government programs, to be integrated in preserving ecoliteracy culture and increasing awareness of ecoliteracy-based character education for students of SMP Negeri 1 Kefamenanu located in the Kefamenanu City area, North Central Timor Regency. This training activity aims to provide scientific contributions in the form of ways, strategies, tips and tips that can be used by students in reading using the SQ3R method and for teachers in applying it through an ecoliteracy approach. The targets achieved in this community service activity, through training and learning actions SQ3R achieved can be shown by the participation of teachers and students, Increased understanding of ecoliteracy-based SQ3R was achieved by students taking tests using the SQ3R method and about 80% complete and there was student awareness to develop and increase interest in reading by applying the SQ3R method at school.